Young people's well-being and the economic crisis: How does parental unemployment and family wealth affect the downturn experience? - Frasquilho, Diana (2016)
Background: Portugal is among the European countriesmost severely hit by the economic recession and the fifth with the highest unemployment rate. Given that adolescents' development is highly influenced by their living contexts, monitoring the repercussions of the economic recession is essential for the evaluation and improvement of their current and future public health. Objective: To investigate youth perceived repercussions of the economic recession, its association with life satisfaction, as well as to assess differences across parental employment status and family perceived wealth. Methods: Data were drawn from the Portuguese 2014 Health Behaviour in School-aged children survey, aWHO collaborative cross-national study, with a nationally representative sample of 2748 students (Mage = 14.7 years ± 1.2; 48% boys). Descriptive statistics and linear regression models were performed. Results: Levels of life satisfaction are lower when young people perceive that the economic recession generated negative lifestyle changes. Having unemployed parents was found to be significantly associated with perceiving such repercussions and family wealth to decrease the perception of repercussions of the recession. Conclusions: Findings enhance our understanding of how Portuguese youth are being affected by the socioeconomic conditions surrounding them. Such information contributes to improve future research and also allow some considerations about the policies aimed at protecting young people'swellbeing during a period of high unemployment and socioeconomic downturn.